Pengaruh Penambahan Alginat Pada Pembuatan Serbuk Terong Belanda ( Cypomandra Betaceae ) - Ledy Bulawan; Tjodi Harlim; Lyse Bulo (Paulus Chem Engineering Journal, 2022)
This study aims todetermine the appropriate ratio between the water and fruit juice as well as the mass of the alginate powder as well as organoleptic test results tamarillo Powder . The method used to study the tamarillo powder is a volume ratio of water : fruit juice ( 1 : 1 , 1 : 2 , 1 : 3 ) with the addition of alginate 0.1 g , 0.2 g , 0.3 g . Analysis was conducted on the organoleptic ( flavor , aroma , color , texture ) and humidity . Based on the research results of data processing tamarillo powder obtained the best results of the organoleptic analysis through expert panelists that the volume ratio of water : fruit juice ( 1 :1 ) with the addition of 0.1 g alginate which give a sense ( strong acids and sweet-sour ) , aroma tamarillo powerful , purple –brown color , and relatively coarse texture with a water content of 0.05 % .